BRAF-Mutated Non-Small Cell Lung Cancer: Current Treatment Status and Future Perspective - Yan, Ningning; Guo, Sanxing; Zhang, Huixian; Zhang, Ziheng; Shen, Shujing; Li, Xingya (Frontiers in Oncology, 2022)
V-Raf murine sarcoma viral oncogene homolog B (BRAF) kinase, which was encoded by BRAF gene, plays critical roles in cell signaling, growth, and survival. Mutations in BRAF gene will lead to cancer development and progression. In non-small cell lung cancer (NSCLC), BRAF mutations commonly occur in never-smokers, women, and aggressive histological types and accounts for 1%–2% of adenocarcinoma. Traditional chemotherapy presents limited efficacy in BRAF-mutated NSCLC patients. However, the advent of targeted therapy and immune checkpoint inhibitors (ICIs) have greatly altered the treatment pattern of NSCLC. However, ICI monotherapy presents limited activity in BRAF-mutated patients. Hence, the current standard treatment of choice for advanced NSCLC with BRAF mutations are BRAF-targeted therapy. However, intrinsic or extrinsic mechanisms of resistance to BRAF-directed tyrosine kinase inhibitors (TKIs) can emerge in patients. Hence, there are still some problems facing us regarding BRAF-mutated NSCLC. In this review, we summarized the BRAF mutation types, the diagnostic challenges that BRAF mutations present, the strategies to treatment for BRAF-mutated NSCLC, and resistance mechanisms of BRAF-targeted therapy.